Is There Gender Disparity in Vascular Access for Hemodialysis with New Percutaneous Systems? A Systematic Review - Hugo Vergara-Pérez; Alejandro Pérez Alba; Pablo Baliño; Asunción Rius Peris; Javier Reque (Kidney and Dialysis)
Background: Historically, a large gender-related disparity in vascular access (VA) has been demonstrated, with there being a lower prevalence of women with arteriovenous fistula (AVF) compared to men, and women have worse maturity rates. The cause of this difference is not entirely clear, although several reasons that could contribute to it have been hypothesized. The emergence of new percutaneous FAV (pFAV) systems could be an alternative for reducing these differences. Objective: This study aims to determine whether there is a gender difference in the creation of AVFs using new percutaneous systems. Material and Methods: A systematic review of the literature was conducted by searching PubMed and Google Scholar using the following terms: “percutaneous arteriovenous fistula”, “endovascular arteriovenous fistula”, and “hemodialysis”. All clinical trials, comparative studies, and descriptive studies involving patients who underwent a pAVF were included. Results: Finally, the review includes 19 studies, comprising 14 retrospective studies and 5 prospective studies. Of these, six studies are comparative, five of which compare pAVFs with surgically created AVFs (sAVFs), and one compares pAVFs performed using different systems with each other. A total of 1269 patients were included in the review. Of the total number of patients, only 414 were women, representing 32.62% of patients. Conclusions: The number of women included in the various studies analyzing pAVF remains very low, representing less than one-third of all patients. Although the causes of this difference are not entirely clear, several reasons have been hypothesized, such as socioeconomic factors, anatomical factors, or even patients’ preferences. Given these results, further studies are needed to try to clarify the reasons for this gender disparity and to establish different strategies to mitigate the barriers faced by women in accessing AVFs.